2017
DOI: 10.15252/embr.201744017
|View full text |Cite
|
Sign up to set email alerts
|

cGAS is activated by DNA in a length‐dependent manner

Abstract: Cytosolic DNA stimulates innate immune responses, including type I interferons (IFN), which have antiviral and immunomodulatory activities. Cyclic GMP-AMP synthase (cGAS) recognizes cytoplasmic DNA and signals via STING to induce IFN production. Despite the importance of DNA in innate immunity, the nature of the DNA that stimulates IFN production is not well described. Using low DNA concentrations, we show that dsDNA induces IFN in a length-dependent manner. This is observed over a wide length-span of DNA, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(180 citation statements)
references
References 38 publications
(62 reference statements)
7
173
0
Order By: Relevance
“…cGAS binding to DNA does not depend on the DNA sequence but does have a minimum length requirement for optimal activation. This ranges from 45 to 70 base pairs at 1 mg/mL to 800‐2000 bp at lower, more physiological DNA concentrations . The binding of cGAS to DNA is cooperative in that when a cGAS dimer binds two strands of DNA, it orients them in such a way that favors binding of subsequent cGAS dimers.…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…cGAS binding to DNA does not depend on the DNA sequence but does have a minimum length requirement for optimal activation. This ranges from 45 to 70 base pairs at 1 mg/mL to 800‐2000 bp at lower, more physiological DNA concentrations . The binding of cGAS to DNA is cooperative in that when a cGAS dimer binds two strands of DNA, it orients them in such a way that favors binding of subsequent cGAS dimers.…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
“…This ranges from 45 to 70 base pairs at 1 mg/mL to 800-2000 bp at lower, more physiological DNA concentrations. 33 The binding of cGAS to DNA is cooperative in that when a cGAS dimer binds two strands of DNA, it orients them in such a way that favors binding of subsequent cGAS dimers. The resulting structure resembles a ladder, with cGAS dimers forming rungs between adjacent DNA strands.…”
Section: Mechanistic Insights Into Cgas Functionmentioning
confidence: 99%
“…Recent studies have revealed the existence of a new intracellular DNA sensing system. Cyclic GMP‐AMP synthase (cGAS), a member of nucleotidyltransferase family, binds dsDNA in a sequence‐independent manner but is activated in a length‐dependent manner (longer than 94‐bp DNA) . cGAS undergoes a conformational change of its catalytic center and then produces the cyclic GMP‐AMP (cGAMP) from ATP and GTP (Figure ) .…”
Section: Rig‐i‐like Receptorsmentioning
confidence: 99%
“…Finally, the work by Luecke et al (2017) underlines the need for a better definition of the antagonistic activities of cytoplasmic DNA nucleases on cGAS sensing of ssDNA, dsDNA and DNA:RNA hybrids in homeostasis and during infections (Fig 1). (1) Different types of DNAs are presented, ordered according to the predicted sensitivity of cGAS to these molecules [1,3,8] (note: a concurrent analysis of these DNA forms has not been performed to date). Short dsDNAs are~45-70 bp long [1], with the 45-bp ISD (interferon stimulatory DNA) being the prototypical sequence used as cGAS ligand (although not representing a physiological DNA produced by the cell).…”
mentioning
confidence: 99%
“…(1) Different types of DNAs are presented, ordered according to the predicted sensitivity of cGAS to these molecules [1,3,8] (note: a concurrent analysis of these DNA forms has not been performed to date). Short dsDNAs are~45-70 bp long [1], with the 45-bp ISD (interferon stimulatory DNA) being the prototypical sequence used as cGAS ligand (although not representing a physiological DNA produced by the cell). (2) Endogenous nucleases limit the cytoplasmic accumulation of DNAs from (1) (note: the type of endogenous DNA processed by SAMHD1 is unknown) [2,6,9,10].…”
mentioning
confidence: 99%